Research of the composition of oxide layer and corn of the klystron cathodes with different degree of development - Vangha, S.O.; Dronov, R.M.; Mats, V.O.; Medvediev, O.V.; Tytov, V.Yu.; Tur, Yu.D.; Chayka, I.O.; Yaroshenko, E.A. (Вопросы атомной науки и техники, 2019)
In accordance with the work program for the restoration of klystrons, a cycle of studies was carried out, which includes X-ray fluorescence analysis of the composition of the emitter layer and core of oxide cathodes with different degrees of operating time. Studies have been conducted to assess the possibility of using and predicting the resource, both restored and used cathodes. Studies were conducted to assess the possibility of using and predicting the resource, both restored and used cathodes. The analysis was performed using a Bruker S8 TIGER WDXRF spectrometer (X-ray tube power 4 kW, Rh-cathode, current up to 170 mA, voltage up to 60 kV), with Spectra Plus software package. Comparative analysis of the data obtained for emitters with different degrees of development can provide a fairly reliable estimate of the efficiency and resource of the cathodes. Згідно з програмою робіт по відновленню клістронів проведено цикл досліджень, який включає в себе ренгенофлюоресцентний аналіз складу шару емітера і керна оксидних катодів з різним ступенем напрацювання. Дослідження було проведено з метою оцінки можливості використання і прогнозування ресурсу як реставрованих, так і катодів, що були вже в експлуатації. Аналіз здійснено за допомогою WDXRF-спектрометра Bruker S8 TIGER (потужність рентгенівської трубки 4 кВт, Rh-катод, сила струму до 170 мА, напруга до 60 кВ), з програмним пакетом Spectra Plus. Порівняльний аналіз отриманих даних для емітерів з різним ступенем напрацювання може забезпечити досить достовірну оцінку працездатності і ресурсу катодів. В соответствии с программой работ по восстановлению клистронов проведен цикл исследований, который включает в себя ренгенофлюоресцентный анализ состава слоя эмиттера и керна оксидных катодов с различной степенью наработки. Исследования проведены с целью оценки возможности использования и прогнозирования ресурса, как реставрированных, так и бывших в эксплуатации катодов. Анализ осуществлен при помощи WDXRF-спектрометра Bruker S8 TIGER (мощность рентгеновской трубки 4 кВт, Rh-катод, сила тока до 170 мА, напряжение до 60 кВ), с программным пакетом Spectra Plus. Сравнительный анализ полученных данных для эмиттеров с различной степенью наработки может обеспечить достаточно достоверную оценку работоспособности и ресурса катодов.